Behavioral Analysis of "Iphone" Brand Loyalty From Brand Experience Mediated by Brand Trust in Surakarta - Siti Fatonah; Nani Irma Susanti (West Science Interdisciplinary Studies, 2023)
The reason people have strong loyalty to smartphones "Iphone" different products is because the quality of the product and the operating system get full trust, recommend products, keep using products, Encourage people to use products to make products very attractive not unconditionally. 100 respondents were taken with Purposive sampling technique. Research results: The influence of Brand Experience on Brand Trust: Behavioral Experience and Sensory Experience hypotheses are accepted, while Intellectual Experience is rejected. The influence of Brand Experience on Behavioral Loyalty: Behavioral Experience, Intellectual Experience and Sensory Experience hypothesis is rejected while Brand Trust is accepted. The effect of Brand Trust on Behavioral Loyalty is hypothesized to be accepted.